Influence of plunger motion profile of high pressure die casting on the casting porosity and solidification rate - Żak, Katarzyna; Dańko, Rafał; Żak, Paweł L.; Kowalczyk, Wojcich (Bulletin of the Polish Academy of Sciences Technical Sciences, 2023)
The high pressure die casting (HPDC) is a technique that allows us to produce parts for various sectors of industry. It has a great application in such sectors as automotive, energy, medicine, as the HPDC allows us to produce parts very fast and very cheaply. The HPDC casting quality depends on many parameters. The parameters among others, are cast alloy alloy metallurgy, filling system design, casting technology elements geometry and orientation, as well as, machine operation settings. In the article, different plunger motion schemes of the HPDC machine were taken into account. Analyses lead to learning about plunger motion influence on the casting porosity and solidification process run. Numerical experiments were run with the use of MAGMASoft® simulation software. Experiments were performed for industrial casting of water pump for automotive. Main parameter taken into account was maximal velocity of the plunger in the second phase. The analysis covered porosity distribution, feeding time through the gate, temperature field during whole process, solidification time. Cooling curves of the casting in chosen points were also analysed. Obtained results allow us to formulate conclusions that connect plunger motion scheme, gate solidification time and the casting wall thickness on the solidification rate and porosity of the casting.